2014
DOI: 10.3109/01443615.2013.834304
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic growth factors in maternal and fetal serum in pregnancies complicated with intrauterine growth restriction

Abstract: The aim of this paper was to study if soluble fms-like tyrosine kinase 1 (sFlt-1), free vascular endothelial growth factor (f-VEGF) and the f-VEGF/sFlt-1 quotient in singleton pregnancies complicated with intrauterine growth restriction (IUGR) are different from controls. This was a case-control study between 18 pregnancies with IUGR and 24 controls. Angiogenic growth factors were measured in maternal serum during pregnancy and in umbilical artery and vein at birth. Results showed that maternal plasma f-VEGF a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
0
10
1
3
Order By: Relevance
“…This is a very interesting find as decreased invasion, decreased PlGF expression, and increased sflt-1 are all hallmarks present during PE and IUGR. 22,[34][35][36] In contrast, when PlGF was added to the Rapamycin treated cells, sflt-1 mRNA expression was restored to control levels. This suggests a role for mTOR phosphorylation and the regulation of PlGF signaling in the invasion of trophoblast cells.…”
Section: Discussioncontrasting
confidence: 51%
“…This is a very interesting find as decreased invasion, decreased PlGF expression, and increased sflt-1 are all hallmarks present during PE and IUGR. 22,[34][35][36] In contrast, when PlGF was added to the Rapamycin treated cells, sflt-1 mRNA expression was restored to control levels. This suggests a role for mTOR phosphorylation and the regulation of PlGF signaling in the invasion of trophoblast cells.…”
Section: Discussioncontrasting
confidence: 51%
“…Previous studies have investigated the relationships between sFlt-1 and/or PlGF and late-onset FGR, but most have utilized methods not readily translated into clinical practice for a general antenatal population. These methods include placental rather than plasma protein analysis [24]; multi-modality integrated models [25, 26]; prior ultrasound diagnosis of SGA [27–33]; and investigation confined to cases of preterm infants [32]. Our large cohort specifically enabled us to compare the utility of sFlt-1, PlGF, and their ratio, in all cases of a SGA infant as well as in a ‘SGA only’ cohort, actively removing the impact of participants with concurrent preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Our results add clarity where previous findings have been inconsistent. Prior to this study, elevated sFlt-1 had been associated with FGR in some animal [34], and human [31, 32, 35, 36] studies with cases of preeclampsia excluded, but not in others [18, 33]. The large numbers in our study and the ability to test levels in both ‘All SGA’ and ‘SGA only’ cohorts have allowed us to confidently define sFlt-1 as a biomarker more specific to preeclampsia, rather than FGR.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies by Borras et al (2014) have reported that maternal plasma free VEGF (f-VEGF) and s-Flt-1 were significantly higher in FGR compared with controls and the f-VEGF/sFlt-1 quotient was significantly lower in the FGR group compared with controls. Although the VEGF family has important roles in normal and complicated pregnancies, the current predictive value of the VEGF family as biomarkers appears to be limited to early onset preeclampsia (Andraweera et al, 2012).…”
Section: Downstream Targets Of Homeobox Genesmentioning
confidence: 98%